IMPLEMENTASI WALL SIT TEST SECARA DARING UNTUK MENGUKUR ASPEK KEBUGARAN JASMANI KEKUATAN OTOT TUNGKAI BAWAH SISWA SMP NEGERI 1 BANGKALAN - Yasin, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Wall Sit as the length of time (seconds) to maintain the mentioned situation/until standing. Physical Fitness is the ability possessed by a person to do quite heavy and long work without experiencing fatigue and the needs met by the body by doing several activities. Lower leg muscle strength as the underlying foundation in the formation of biomotor components, important physical components are needed to achieve optimal performance. This study is to measure the physical fitness aspect of lower leg muscle strength by implementing the wall sit test on students at SMPN 1 Bangkalan. This quantitative research is a descriptive research type. The population is grade VII students of SMPN 1 Bangkalan, with a sample of grade VII of 30 students. In proving and analyzing this, the wall sit test instrument is used. For the validity of the instrument, the reliability test, normality test, homogeneity test and Paired Sample T-test are used. The results of the study based on hypothesis testing using SPSS Windows 2.1. Hypothesis obtained sig. value (2-tailed) is 0.000 <0.05 that the first test result with the second test result has a difference using the implementation of the wall sit test because of the significant difference between the first test result and the second test result on the strength of the lower leg muscles of class VIII students of SMPN 1 Bangkalan. From the previous results it is known that the wall sit test can measure the physical fitness aspect of the strength of the lower leg muscles of SMPN 1 Bangkalan students.